Magnetic Domains Investigating the Structure, Characteristics, and Properties of Thiosemicarbazone Ligands - poladian, qumars; Juyan, Mohammad Yusof (Journal of Natural Sciences – Kabul University, 2023)
This article discusses the definition, history, characteristics, and properties of thiosemicarbazone ligands. These compounds exhibit significant biological activities, including antiviral, antifungal, antibacterial, antitumor, anticancer, antioxidant, and insulin-mimicking properties. Coordination of thiosemicarbazone ligands occurs through donor atoms such as sulfur, nitrogen, and sometimes a third donor atom. The study's findings indicate that the presence of amide, amine, and thione groups makes thiosemicarbazones potential polydentate ligands. The aim of this review, which employs a descriptive-analytical approach, is to provide a comprehensive definition of these ligands, discuss their characteristics, structural features, and coordination behaviors.